FORMULATION AND EVALUATION OF GLIBENCLAMIDE GEL FOR TRANSDERMAL DRUG DELIVERY - ANWAR, NOSHEEN; JAN, SYED UMER; GUL, REHMAM (International Journal of Current Pharmaceutical Research, 2020)
Objective: The purpose of the recent study was to formulate glibenclamide gels for transdermal drug release, and to evaluate the oleic acid effect on the release of the preparations. Methods: Oleic acid was used at a range of concentrations in the gel formulations and its effects observed in Glibenclamide gel using In vitro release of drug was done in Franz diffusion cells, whereas pH 7.4 Phosphate buffer was used for release studies. Formulations were characterized by clarity, pH, homogeneity, viscosity, spreadabilty, skin irritation, drug content, stability studies. Scanning calroimetry analysis (SCA) and XRD studies were performed to assess the physical and chemical interactions. Results: Release profiles in vitro were observed. The released quantity of drug recovered from the glibenclamide gel after the addition of 1% oleic acid, increased with increasing concentration of the enhancer that is oleic acid. Whereas drug quantity recovered in the receptor solvent was 69.999% of Glibenclamide gel having 3% oleic acid. All the formulation were physicochemically stable. The data was statistically analyzed by using SPSS and DD solver. Conclusion: The drug is released and the oleic acid does enhance the release of the drug with the increase in its concentration.